(untitled) (Research, Society and Development, 2020)
Objective: to characterize the profile of users and caregivers treated in a home care program; and identify the nursing actions. Method: observational descriptive, documentary, based on a survey of 129 medical records in a Home Care Service. It has been collected sociodemographic, clinical information and the nursing actions. Results: Female users prevailed 63,56% (82), aged between 60 and 79 years old 48% (62), coming from spontaneous demand 61,2% (79), with up to one year of enrollment 38,7% ( 50) and presenting motor sequelae of stroke 43,4% (56). The caregivers were mostly women, 90,75% (108), family members, 87,5% (113). The nurse’s actions involved: gauging vital signs, capillary blood glucose (127) collecting venous blood, and diuresis for laboratory tests (66) and reporting general nursing guidelines for the family / caregiver (54). Conclusion: The research allowed to characterize users and caregivers of home care and to identify the difficulty of articulation with the other services of the Health Care Networks. The development of permanent education in home care and gerontology is recommended, and the creation of strategies that optimize communication in the services.